Relationship and community factors related to better mental health following child maltreatment among adolescents. (August 2017) - Cheung, Kristene; Taillieu, Tamara; Turner, Sarah; Fortier, Janique; Sareen, Jitender; MacMillan, Harriet L.; Boyle, Michael H.; Afifi, Tracie O.
Abstract: Research on factors associated with good mental health following child maltreatment is often based on unrepresentative samples and focuses on individual-level factors. To address these gaps, the present study examined the association between relationship- and community-level factors and overall mental health status among adolescents with and without a history of maltreatment in a representative sample. Data were drawn from the National Comorbidity Survey of Adolescents (NCS-A; n = 10, 148; data collection 2001–2004); a large, cross-sectional, nationally representative sample of adolescents aged 13–17 years from the United States. Having supportive parent and family relationships were significantly associated with good mental health (AOR ranging from 2.1 to 7.1). Positive community and school experiences were also significantly associated with good mental health (AOR ranging from 2.0 to 9.8). In most models, support from friends and siblings was not related to better mental health. Factors to be tested for efficacy in interventions targeted to adolescents with a history of child maltreatment include encouraging supportive parent and family relationships, and fostering positive community and school experiences.